اللسانيات التطبيقية وعلاقتها بالاكتساب اللغوي - ناصر, فضيلة (كلية الأدب العربي والفنون, 2024)
اللسانيات التطبيقية تركز على تطبيق النتائج والمفاهيم اللغوية في مجالات متعددة مثل تعليم اللغة، والترجمة، وتكنولوجيا المعلومات، والاتصالات وغيرها، وهي تستفيد من العلوم الأخرى مثل علم النفس، وعلم الاجتماع.... في فهم وتطبيق اللغة، إذ يقتضي البحث جانب مهم من الدراسة وهو الاكتساب اللغوي للطفل اللغة الذي حاز على اهتمام العديد من الباحثين وعليه فاكتساب الطفل للغة هي عملية فطرية عفوية غير شعورية يقوم بها الطفل، ونقصد في الاكتساب اللغوي عند الطفل هو عملية تلقائية يقوم بها دون معرفة مسبقة بقواعد اللغة وقوانينها: حيث يعتمد على نفسه مستعينا بالقدرات التي زودها الله تعالى بها والتي تمكنه من اكتساب اللغة في فترة قصيرة. Appliedlinguisticsfocuses on applyinglinguisticfindings and concepts in multiple fieldssuch as languageteaching, translation, information technology, communications, etc. itbenefitsfromother sciences such as psychology and sociology…. in understanding and applyinglanguge, as researchrequires an important aspect of thestudy. It is the child'slinguistic acquisition of language, which has received the attention of manyresearchers. Accordingly, the child's acquisition of languageis an innate, spontaneous, subconsciousprocesscarried out by the child. By linguistic acquisition, wemeanthatchildis an automaticprocessthathecarries out withoutpriorknowledge of the rules and laws of the language: he relies on himself, usinghisabilities. Whichgodalmightyprovidedhimwith, whichenableshim to acquire the language in a short period.
Keywords: اللسانيات التطبيقية، الاكتساب، اللغة، الاكتساب اللغوي; appliedlinguistics, acquisition, language, linguistic acquisition.